2019
DOI: 10.3389/fpsyg.2019.00669
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Analysis of the Interactions During Clinical Supervision

Abstract: This study intends to analyze some skills trained during supervision. In it we describe sets of interactions (based on the American Psychological Association [APA], 2006 ; competency domains) happened between the supervisor and the supervisee during the supervision process. Interactions from twelve supervisor-supervisee dyads during asynchronous and direct, and individual and group supervision sessions were video recorded for this purpose. The recordings helped to determine, classify, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Supervising people is a learning process that deals with different kinds of characters and people, so the supervisor develops ways of dealing with such people. Novoa-Gómez et al [27] also revealed in a similar study that supervisors deal with supervisees from different backgrounds, hence, learn to embrace diversity. They however opined that; skills related to the clinical supervisors' duties should be extensively conceptualized.…”
Section: Discussionmentioning
confidence: 83%
“…Supervising people is a learning process that deals with different kinds of characters and people, so the supervisor develops ways of dealing with such people. Novoa-Gómez et al [27] also revealed in a similar study that supervisors deal with supervisees from different backgrounds, hence, learn to embrace diversity. They however opined that; skills related to the clinical supervisors' duties should be extensively conceptualized.…”
Section: Discussionmentioning
confidence: 83%
“…referred that the most time was spent on evaluation, intervention, and conceptualization skills by supervisors during educational, clinical supervision, and the minimum time was related to emotional and interpersonal processes. [ 26 ] In the study by Del Aram (2006) and? Ghafourifard et al .…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the current study was to adapt and validate the S-SRQ [2] for use with GP registrars within the Australian GP training context. The relationship between clinical supervisors and registrars has been demonstrated to be vital in fields such as clinical psychology [4,34,35]. The therapeutic alliance between supervisors and registrars in psychology is considered to be analogous to the educational alliance in medical training [1,3,[36][37][38] highlighting the need to consider supervisory relationships in medical training.…”
Section: Discussionmentioning
confidence: 99%